Respostas

2014-03-11T21:22:08-03:00
2x² + 14x + 24 = 0
a = 2             
b = 14
c = 24
           Δ = b² - 4ac
           Δ = 14² - 4 . 1 . 24
           Δ = 196 - 96
           Δ = 100
                      x = - b ± √Δ 
                                2a
                      x = - 14 ± √100
                                 2 . 2
                      x' = - 14 - 10 = - 24 (simplifica-se ambos por 2 (divisão)) = - 12 (simplifica-                                       4           4                                                            2       
                                     se por 2 (divisão)) = - 6 (simplifica-se por 3 (divisão)) = - 2 (sim-
                                                                    2                                                2
                                     plifica-se por 2 (divisão)) = - 1  
                                                                             2
                      x" = - 14 + 10 = - 4 = - 1                   
                                   4           4